Robots at Work: Automatable and Non Automatable Jobs - Cecily Josten; Grace Lordan (Institute of Labor Economics (IZA), 2019)
This study builds on Autor and Dorn's (2013) classification of automatable work at the three-digit occupation code level to identify additional jobs that will be automatable in the next decade by drawing on patent data. Based on this new classification the study provides estimates of the share of jobs that we expect to be automatable in the EU and across 25 individual countries. The study highlights that aspects of 47% of jobs will be automatable over the next decade, with 35% of all jobs being fully automatable. It also provides some evidence that 'thinking' and 'people' skills will become increasingly important for the fourth industrial revolution. The study puts emphasis on the fact that these estimates are based on static models. Assuming that some of the rents from labor technology will filter back into the economy it is expected that other occupations will expand in number as people consume more goods and services.
Keywords: J23; J24; O20; 330; skills; labor markets; robots